Киевский национальный университет имени Тараса Шевченко - Нестеряк, Юлия; Цисак, Войцех (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2018)
The article discusses how the state of information security in Ukraine affects information security in Europe. In particular, it analyzes the information threats existing in the Ukrainian information space, which arouse the concern of EU member states, and others. The formation of the information security of Ukraine is considered in the context of the modern challenges to information policy in the conditions of hybrid warfare. The recommendations offered by the authors regarding the improvement of the level of information security are based on the experience of European countries in counteracting Russian propaganda.